INTEGRASI ANALISIS MDS-RAPFISH DALAM PERENCANAAN KEBIJAKAN PENGURANGAN RISIKO BANJIR DI DAS KURANJI [INTEGRATION OF MDS-RAPFISH ANALYSIS IN POLICY FORMULATION FOR FLOOD RISK REDUCTION IN THE KURANJI WATERSHED] - Syafri, Rifki Randa; Frinaldi, Aldri; Umar, Genius; Lanin, Dasman; Rembrandt, Rembrandt; Umar, Iswandi (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to integrate the results of sustainability analysis using the Multidimensional Scaling–RAPFISH approach into the policy planning process for flood risk reduction in the Kuranji Watershed, Padang City. Five strategic dimensions—economic, environmental, social, infrastructure, and institutional—were analyzed to provide a holistic view of sustainability. Primary data were collected through interviews and questionnaires with stakeholders, while secondary data came from planning documents and policies. The analysis revealed that four of the five dimensions are in the less sustainable category, with index scores ranging from 37.69 to 42.22. Only the institutional dimension was considered moderately sustainable, with a score of 51.77. The average sustainability index across all dimensions was 41.99, indicating an overall status of low sustainability. Leverage and Monte Carlo analyses were used to identify the most influential attributes. The infrastructure dimension had the lowest index, largely affected by the availability of evacuation routes, early warning systems, and emergency logistics. The RAPFISH model demonstrated strong validity and reliability, supported by stress values below 0.15 and R² values near 1. Monte Carlo simulations showed minimal differences, confirming model robustness. These findings suggest that MDS-RAPFISH is a valuable tool for evidence-based policy planning, enabling prioritization of interventions and formulation of adaptive, integrated strategies. This approach can help policymakers identify critical leverage points and design flood risk reduction policies that address the socio-environmental complexities of the Kuranji Watershed, while contributing to the achievement of Sustainable Development Goals (SDGs).